Development of a Conceptual Framework for Implementing Learning Management System (LMS) in Higher Education: An Empirical Validation Study - Rivaldi Rizalul Akhsan; Dion Lamilga Sudiono Putra; Dana Indra Sensuse; Deden Sumirat Hidayat; Erisva Hakiki Purwaningsih (Faculty of Computer Science Universitas Indonesia, 2025)
Higher education institutions today face increasingly complex challenges in adopting and implementing Learning Management Systems (LMS) to improve student learning experiences. Although previous research regarding LMSs exists, it has not fully explored the findings of their conceptual framework through empirical studies of Critical Success Factors (CSFs). This research provides in-depth details about the development of a conceptual framework designed to guide the LMS implementation process in higher education settings. The Systematic Literature Review (SLR) method is used to identify and introduce the main elements in this conceptual framework. Furthermore, the conceptual framework was validated through a series of questionnaires distributed to experts in the fields of education and information technology. The results of this research show that the conceptual framework developed covers important stages in LMS implementation, from planning to evaluation. Empirical validation carried out involving experts proves that the conceptual framework developed is valid as an instrument for implementing LMS in a higher education environment. The conclusions of this research provide valuable guidance for LMS implementation in higher education.